Annexin‐A1: The culprit or the solution?. Issue 1 (1st March 2022) - Kelly, Lauren; McGrath, Sarah; Rodgers, Lewis; McCall, Kathryn; Tulunay Virlan, Aysin; Dempsey, Fiona; Crichton, Scott; Goodyear, Carl S.
Abstract: Annexin‐A1 has a well‐defined anti‐inflammatory role in the innate immune system, but its function in adaptive immunity remains controversial. This glucocorticoid‐induced protein has been implicated in a range of inflammatory conditions and cancers, as well as being found to be overexpressed on the T cells of patients with autoimmune disease. Moreover, the formyl peptide family of receptors, through which annexin‐A1 primarily signals, has also been implicated in these diseases. In contrast, treatment with recombinant annexin‐A1 peptides resulted in suppression of inflammatory processes in murine models of inflammation. This review will focus on what is currently known about annexin‐A1 in health and disease and discuss the potential of this protein as a biomarker and therapeutic target. Abstract : Annexin‐A1 has a well‐defined anti‐inflammatory role in the innate immune system, but its function in adaptive immunity remains controversial. This glucocorticoid‐induced protein has been implicated in a range of inflammatory conditions and cancers, as well as being found to be overexpressed on the T cells of patients with autoimmune disease. This review will summarise what is currently known about ANXA1 in terms of its structure and function and discuss current research examining the role of ANXA1 and its receptors in disease. The potential of ANXA1 and its receptors as biomarkers and therapeutic targets in disease will also be discussed Special Issue: No.